Youth justice workers' views on implementing policy: interview data - Phoenix, Joanna (UK Data Service, 2016)
This set of transcripts consists of interviews with youth justice workers in two local authorities. It describes their day to day working lives, their understanding of the relationship between policy and practice and their training and training needs. Ways of dealing with young people in trouble with the law have been the object of (often intense) popular and political debate for at least two centuries. Despite this, there is no consensus amongst policy makers or criminological scholars about the most appropriate responses. In England, where this study is located, youth justice policies have been in a more or less constant state of change for two decades. Although youth justice practitioners must learn to make professional judgements in an environment of rapidly changing policy, surprisingly little is known about how they interpret and implement policy. Even less is known about the extent to which the training and education they receive prior to becoming youth justice workers prepares them to manage their everyday working lives. This research project aims to plug this gap in knowledge by conducting research with two youth offending services in England. Approximately one hundred qualitative, in-depth interviews were conducted with the full range of youth justice workers in the studied locations, excluding administrative and sessional workers and volunteers. This included: operational managers and youth justice practitioners.